Analisis Pemakaian Listrik pada Pompa Drainage Unit dengan Menggunakan New Quality Tools - Handika, Firdanis Setyaning; B. Barnadi, Abdullah (Jurnal Sistem dan Manajemen Industri, 2017)
Every company tries to minimize the cost of production to get the product with the price of flocking. A Chemical Company in Cilegon has a production cost reduction program. However, in the process of creation, still found some factors that cause high production costs, especially the cost of electricity in pumping equipment. This study aims to determine the causes of high electricity consumption in the drainage pump unit, provide suggestions for improvement and evaluate the results of revision. This research uses some new quality tools consisting of affinity diagrams, interrelationship diagrams, matrix diagrams, tree diagrams, and Process Decision Program Chart (PDPC). Based on the results of the research, the factors causing high electricity consumption in the drainage pump unit are DCS-Man forgot to stop at the G-1875 pump, the C-1851 sealing output goes to the slimy pit, and the G-1871 sealing output goes into the dirty hole. The remedial step is to move the C-1851 sealing output from the muddy ditch to the clean trench, moving the G-1871 sealing output from the filthy ditch to the clean ditch, fixing the leak in the sample product box, and the G-1875 pump made auto start-stop. These drainage improvements resulted in drainage units operating two times per week from the previous 18 times per week or decreased by 89% and can save as much as Rp 1,677,205 per year.